Discovery of polymethoxyflavones as potential cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX) and phosphodiesterase 4B (PDE4B) inhibitors. (4th July 2022) - Md Idris, Muhd Hanis; Mohd Amin, Siti Norhidayah; Mohd Amin, Siti Norhidayu; Wibowo, Agustono; Zakaria, Zainul Amiruddin; Shaameri, Zurina; Hamzah, Ahmad Sazali; Selvaraj, Manikandan; Teh, Lay Kek; Salleh, Mohd Zaki
Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely prescribed to treat inflammatory-related diseases, pain and fever. However, the prolong use of traditional NSAIDs leads to undesirable side effects such as gastric, ulceration, and renal toxicity due to lack of selectivity toward respective targets for COX-2, 5-LOX, and PDE4B. Thus, targeting multiple sites can reduce these adverse effects of the drugs and increase its potency. A series of methoxyflavones (F1 –F5 ) were synthesized and investigated for their anti-inflammatory properties through molecular docking and inhibition assays. Among these flavones, only F2 exhibited selectivity toward COX-2 (Selectivity Index, SI: 3.90, COX-2 inhibition: 98.96 ± 1.47%) in comparison with celecoxib (SI: 7.54, COX-2 inhibition: 98.20 ± 2.55%). For PDEs, F3 possessed better selectivity to PDE4B (SI: 4.67) than rolipram (SI: 0.78). F5 had the best 5-LOX inhibitory activity among the flavones (33.65 ± 4.74%) but less than zileuton (90.81 ± 0.19%). Docking analysis indicated that the position of methoxy group and the substitution of halogen play role in determining the bioactivities of flavones. Interestingly, F1 –F5 displayed favorable pharmacokinetic profiles and acceptable range of toxicity (IC50 >70 µM) in cell lines with the exception for F1 (IC50 : 16.02 ± 1.165 µM). This study generated valuable insight in designing new anti-inflammatory drug based on flavone scaffold. The newly synthesized flavones can be further developed as future therapeutic agents against inflammation. Graphical Abstract: UF0001